Geologic Map in GIS - Jasna Šinigoj; Marko Komac (Geologija, 2002)
Gathering and analysing of the geological data of a certain area is a procedure where various spatial data are related and processed. The aim of a geologist is to determine the model that will represent the natural conditions by its most and will help him solve relations between data. Usually geological data have various origins and are for the purpose of modelling merged, united or joined together. The result is a geologic map that forms a foundation for the comprehension of the real geological conditions of a given area.The paper presents conceptual and logical model of the geological maps in the GIS environment. Here characteristics of the database, the standard procedures for the data input and their quality control procedures are shown.